HUBUNGAN PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG GIZI SEIMBANG SELAMA HAMIL DENGAN KEJADIAN BBLR - Woro Tri Utami, Woro Tri Utami; Waqidil Hidayah, Waqidil Hidayah; Ika Junita, Ika Junita (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2013)
Knowledge of mothers on nutrition is crucial to the future of children and families. The purpose of the study to analyze the relationship of knowledge maternal 3rd trimester about balanced diet for pregnant with BBLR incident . Survey design used analytic approaches Prospective ( Cohort ) , sampling techniques using simple random sampling . Independent Variable knowledge maternal 3rd trimester about balanced nutrition and dependent variable BBLR incident . Instrument research questionnaires and observation . Data processing and editing, coding, scoring , and tabulating .Test data analysis and contingency coefficient The results with the results of statistical tests Koofisient Kontinengensi with significant P value ( 0.000 ) < ? ( 0.05), then H0 is rejected, which means there are relations knowledge maternal 3rd trimester about balanced diet for pregnant with BBLR incident .In conclusion there is significant relationship between knowledge maternal 3rd trimester about balanced diet while pregnant with BBLR incident . Respondents expected to be more active in seeking information about a balanced diet during pregnancy in order to prevent BBLR . Keywords: Knowledge , BBLR , Pregnant Women